META-ANALISIS PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT TERHADAP HASIL BELAJAR DI SEKOLAH DASAR - Ririn Mustaqimatul Luthfiyah; Mohammad Taufiq; Muhammad Syamsul Ghufron; Akhwani Akhwani (Universitas Negeri Medan, 2020)
This study aims to describe the use of the Teams Games Tournament learning model towards learning outcomes in elementary schools. The method used in this study is the meta-analysis method. This research begins by formulating the topic to be investigated, then making the formulation of the problem and the purpose of the research, at the next stage collecting relevant articles to collect data. The data was obtained from online journal searches through Google Scholar. The keywords used are